Sikap over protective orang tua dan kepercayaan diri remaja - Bawinda Sri Lestari; Erlina Mamus (INNER: Journal of Psychological Research, 2022)
Self-confidence is a positive attitude of an individual that enables him to develop a positive assessment, both of himself and of the environment or situation he faces. The background of this research is that there are still students who lack confidence in every day life, aspecially in a school environment which is indicated by students feeling afraid to express opinions, cheating or not sure about their own work and students who nervous when appearing in front of the class. The purpose of this study was to determine the relationship between parents’ overprotective attitude and self-confidence in adolescents. This research is a quantitative research. The sampling technique used a random Sampling technique. The results of the study through the Spearman Brown correlation test showed so that there was a very significant negative correlation between parents’ overprotective attitudes and self-confidence in adolescents. The higher the parent’s overprotective attitude, the lower the self-confidence in adolescents. Conversely, the lower the overprotective attitude of parent’s, the higher the self confidence of adolescents. Looking at the results, the hypothesis states that there is a relationship between parent’s overprotective attitudes and self-confidence in adolescents. Keywords: Over Protective Parents, Self Confidence, Adolescent